Characterization of the Oral Microbiome in Wearers of Fixed and Removable Implant or Non-Implant-Supported Prostheses in Healthy and Pathological Oral Conditions: A Narrative Review - Francesco D’Ambrosio; Biagio Santella; Maria Pia Di Palo; Francesco Giordano; Roberto Lo Giudice (Microorganisms, 2023)
Oral commensal microorganisms perform very important functions such as contributing to the health of the host. However, the oral microbiota also plays an important role in the pathogenesis and development of various oral and systemic diseases. The oral microbiome may be characterized by a higher prevalence of some microorganisms than others in subjects with removable or fixed prostheses, depending on oral health conditions, the prosthetic materials used, and any pathological conditions brought about by inadequate prosthetic manufacturing or poor oral hygiene. Both biotic and abiotic surfaces of removable and fixed prostheses can be easily colonized by bacteria, fungi, and viruses, which can become potential pathogens. The oral hygiene of denture wearers is often inadequate, and this can promote oral dysbiosis and the switch of microorganisms from commensal to pathogens. In light of what emerged from this review, fixed and removable dental prostheses on teeth and on implants are subject to bacterial colonization and can contribute to the formation of bacterial plaque. It is of fundamental importance to carry out the daily hygiene procedures of prosthetic products, to design the prosthesis to facilitate the patient’s home oral hygiene practices, and to use products against plaque accumulation or capable of reducing oral dysbiosis to improve patients’ home oral practices. Therefore, this review primarily aimed to analyze the oral microbiome composition in fixed and removable implant or non-implant-supported prostheses wearers in healthy and pathological oral conditions. Secondly, this review aims to point out related periodontal self-care recommendations for oral dysbiosis prevention and periodontal health maintenance in fixed and removable implant or non-implant-supported prostheses wearers.